2009
DOI: 10.1080/10810730902805788
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Internet-Based, Stage-Matched Message Intervention on Young Taiwanese Women's Physical Activity

Abstract: A web-based, stage-matched message intervention was designed in order to see the effect on the physical activity of young Taiwanese women with regard to several variables. The intervention was guided by the Transtheoretical Model (TTM) and was evaluated using a pre-post-test control group design. One hundred thirty female freshmen, enrolled in a nursing class in a university in Taipei, completed the survey at three different points in time. They were assigned to three groups: an experimental group with stage-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 25 publications
2
31
0
1
Order By: Relevance
“…In the one remaining study, the stage of change was not identified during assessment or evaluation phases, however an intervention plan was formulated using other TTM concepts rather than stage of change. There were six studies comparing the outcome of the stage-matched intervention with that of no stage-matched intervention [28][29][30][31][32][33]. Findings from all of the studies except one [28] showed that the stage-matched intervention is more effective than no stage-matched intervention.…”
Section: Use Of Stage-matched Interventionmentioning
confidence: 97%
“…In the one remaining study, the stage of change was not identified during assessment or evaluation phases, however an intervention plan was formulated using other TTM concepts rather than stage of change. There were six studies comparing the outcome of the stage-matched intervention with that of no stage-matched intervention [28][29][30][31][32][33]. Findings from all of the studies except one [28] showed that the stage-matched intervention is more effective than no stage-matched intervention.…”
Section: Use Of Stage-matched Interventionmentioning
confidence: 97%
“…The literature indicated that researchers rarely had control of users' actual completion of the interventions. 64 Researchers had little control over the users' access to other Web sites (to prevent contamination), and they rarely identified nonverbal cues. 8,19 The reliability/ credibility of the data provided by users largely depended on the users' willingness and honesty.…”
Section: Logistics For Usersmentioning
confidence: 99%
“…The retention rates were about 50% across the sub-ethnic groups by the end of the 3-month intervention, which is similar to other Web-based studies in the literature. 3234 The control group was asked to use only the Internet resources related to daily life (e.g., news in Asian countries, Asian businesses in the U.S.) and the American Cancer Society website while the intervention group was asked to use both the Internet cancer support group and the Internet resources (those related to daily life and those by the American Cancer Society).…”
Section: The Study As the Case Examplementioning
confidence: 99%